Effect of parallel LPG fuelling in a methanol fuelled SI engine under variable compression ratio. (15th January 2022) - Dinesh, M.H.; Pandey, Jayashish Kumar; Kumar, G.N.
Abstract: In the present experimental study, five LPG fractions from 25% to 45% based on total energy are tested in a methanol fuelled SI engine at compression ratios (CR) varying from 12 to 15. Results are affirmative towards methanol/LPG dual fuel. The brake power, brake thermal efficiency, and volumetric efficiency are found to increase by 51%, 21.2%, and 13% respectively by changing from 25% LPG fraction at CR12 to 45% LPG fraction at CR15. The flame development period is found to decrease with CR and LPG, while the flame propagation period and total combustion duration are found to decrease with CR but increase with LPG. The maximum cylinder pressure and net heat release rate are found to increase by 101% and 27.8% respectively and advanced. CO emissions are found to decrease with CR while increase with LPG fraction. HC is found to decrease with LPG as well as CR. CO2 emissions are found to increase continuously with increasing LPG fractions and CR. The NOx emissions are also found to increase explicitly with LPG and CR, a net 209% increase in it is found 25% LPG at CR 12–45% LPG at CR15. Highlights: Methanol is a bio-produce with excellent qualities best suit for SI engine. Low heating value and high latent heat drawbacks can be overcome LPG blending. The increasing CR results in better performance and fuel economy. With a high H/C ratio, carbon emission is reduced with methanol-LPG blends. The NOx emissions are found to increase with increasing LPG blend strength.